Vascular Stem Cells in Vascular Remodeling and Diseases - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Blood vessels are a source of stem and progenitor cells, which likely contribute to a variety of vascular processes and diseases. Emerging concepts in this field could influence therapeutic approaches to diseases of blood vessels such as atherosclerosis.CONTENT: Vascular Stem Cells (VSCs) field is only beginning to emerge, and thus, many issues regarding VSCs’s identity and function remain poorly understood. In fact, even after decades of intensive research, Mesenchymal Stem Cells (MSC), which is suggested to be VSCs, is still having many outstanding issues of its own. And, on top of this, likewise decades-long intensive pericyte research has not been able resolve the identity issue. While favors Adventitial Progenitor Cells (APCs) over pericytes as the likely VSC candidate, it should be pointed out that currently the opposite view (i.e., pericytes as VSCs) is more prevalent, and many excellent reviews, including a recent one, have discussed this issue extensively.SUMMARY: It has been postulated that, within the vasculature, APCs could differentiate into pericytes (CD34- CD31- CD140b+ SMA-), endothelial cells (CD34+ CD31+ CD140b- SMA-), and smooth muscle cells (SMCs) (CD34- CD31- CD140b- SMA+); and during tissue expansion or repair, APCs could also differentiate into tissue-specific cell types (e.g., muscle and fat) Thus, in vitro, APCs fulfill all criteria for being VSCs. Meanwhile, in vivo evidence is still limited and will require further investigation.KEYWORDS: vascular stem cells, VSC, mesenchymal stem cells, MSC, endothelial progenitor cells, EPC, adventitial progenitor cells, APC